2006
DOI: 10.1002/dvdy.20916
|View full text |Cite
|
Sign up to set email alerts
|

Birth and death of cells in limb development: A mapping study

Abstract: Cell death and cell proliferation are basic cellular processes that need to be precisely controlled during embryonic development. The developing vertebrate limb illustrates particularly well how correct morphogenesis depends on the appropriate spatial and temporal balance between cell death and cell proliferation. Precise knowledge of the patterns of cell proliferation and cell death during limb development is required to understand how their modifications may contribute to the generation of the great diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
104
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(116 citation statements)
references
References 70 publications
12
104
0
Order By: Relevance
“…In E13.5, normal limb buds, pH 3-positive cells were scarce in the interdigits and in the condensed chondrogenic elements ( Fig. 5A; Fernandez-Teran et al, 2006). Interestingly, in the mutant limb the abnormal area of cell death at the base of digits 2/3 was devoid of mitotic cells (Fig.…”
Section: Abnormal Cell Death In Mutant Autopodsmentioning
confidence: 92%
See 1 more Smart Citation
“…In E13.5, normal limb buds, pH 3-positive cells were scarce in the interdigits and in the condensed chondrogenic elements ( Fig. 5A; Fernandez-Teran et al, 2006). Interestingly, in the mutant limb the abnormal area of cell death at the base of digits 2/3 was devoid of mitotic cells (Fig.…”
Section: Abnormal Cell Death In Mutant Autopodsmentioning
confidence: 92%
“…To investigate the cause of this defect, we analyzed cell death in limb buds of mutant and normal littermates by TUNEL during the time at which the digits are specified (from E11.5 to E13.5). The distribution of apoptotic cells in mutant limb buds at E11.5 and E12.5 was as described (Fernandez-Teran et al, 2006) for normal limb buds (data not shown). However, at E13.5 an abnormal area of cell death was detected at the base of digits 2/3 in mutant forelimb buds (arrow in Fig.…”
Section: Abnormal Cell Death In Mutant Autopodsmentioning
confidence: 92%
“…The limb bud was chosen because it has been one of the embryonic structures studied in more detail in relation with PCD (see Zuzarte-Luis and Hurle, 2002;Fernandez-Teran et al, 2006). We previously reported that cathepsin B and D expression appeared very precise markers for the anterior and posterior areas of cell death (ANZ and PNZ) and also for the areas of interdigital cell death (INZ; ZuzarteLuis et al, 2007).…”
Section: New Areas Of Cell Death In the Developing Limbmentioning
confidence: 99%
“…Despite its originality, this approach had a major disadvantage: it assumed uniform expansion along the P-D axis. It is now known that this is not the case, at least for the developing mouse limb (Boehm et al, 2010), while less clear evidence exists for the chicken limb (Hornbruch and Wolpert, 1970;Fernandez-Teran et al, 2006). The second problem is the limited ability to recognize which elements are formed from the graft and which from the host.…”
Section: Introductionmentioning
confidence: 99%